Training of Sputum Microscopy Improves the Smear Quality and Slide Positivity Rate for Pulmonary Tuberculosis Diagnosis - Dede Kurniawan; Ning Rintiswati; Dibyo Pramono (Tropical Medicine Journal, 2013)
ABSTRACT Introduction: Microscopic examination of sputum is a key component of the diagnosis of pulmonary tuberculosis. The accuracy of this method is influenced by quality of laboratory and human resources. Indonesia is one of endemic country for pulmonary tuberculosis. Efforts to improve the quality of microscopic examination are needed, including training of human resources.Objectives: To determine impact of microscopic examination training to smear quality and slide positivity rate.Methods: This work is an analytic quasi experimental research. The research was involved 18 laboratory technician. Subjects were divided in to experimental and control group, which was consisting 9 technicians in each group. The differences of smear quality and slide positivity rate were analyzed by using independent t-test and Mann-Whitney test with 95% of Confident Interval.Results: Training increased the knowledge of laboratory technician (40.7 points) and the smear quality. Specimen quality was increased 90 points, staining 84.4, cleanness 85.6, thickness 91.1, smear size 88.9, evenness 87.8 and increase the average of smear readings score test 22 points. The mean of smear quality and slide positivity rate of the experimental group were higher than control group. Statistical test of smear quality between eksperimental group with contol group were: specimen quality p=0.03, staining quality p=0.03, cleanness p=0.02, thickness p<0.001, size p<0.001, good evenness p<0.001, and slide positivity rate p=0.02Conclusion: The mean of smear quality and slide positivity rate of the experimental group were higher than control group. There were significant differences of smear quality and slide positivity rate between experimental group with control group at 3 months after training.Keywords: training, sputum microscopy, smear quality, slide positivity rate, tuberculosis